Offshore drilling blowout risk model – an integration of basic causes, safety barriers, risk influencing factors and operational performance indicators. Issue 1 (3rd April 2018) - Perez, Pedro; Dalu, Guido; Gomez, Natalia; Tan, Henry
Abstract: Offshore drilling is an activity inherent to the oil and gas industry as it is essential for confirming the economic feasibility of hydrocarbon reservoirs. However, operational uncertainties and risks inherent to typical major accident hazards are associated with the performance of this activity, where blowouts are assumed to be one of the major contributors to risk in offshore drilling. This paper presents an accident precursor risk model for offshore drilling blowouts that integrates the blowout basic causes, safety critical barriers and elements, risk influencing factors (RIFs) including human and organisational factors (HOFs), and operational performance indicators (OPIs). The method, which was adopted to design the model and allow its customisation for reflecting the characteristics of any drilling rig, well and operation is also described and demonstrated using a theoretical example. The model is hybrid, as it combines bow-tie diagram (fault tree and event tree) with directed acyclic graphs (DAGs), to account for the effect of the RIF on the performance of safety barriers through the direct observation of pre-defined OPI. Abbreviations: BHA bottom hole assembly BOP blowout preventer BORA barrier and operational risk analysis DAG directed acyclic graph DP dynamically positioned ECD equivalent circulating density G&G geological and geophysical HC hydrocarbon HOFs human and organisational factors HP/HT high pressure/high temperature HSE health, safety and environment IADC International Association of Drilling Contractors IMO International Maritime Organisation IRPA individual risk per annum ISM International Safety Management Code ISO International Standard Organisation LMRP lower marine riser package LWD logging while drilling MODUs mobile offshore drilling units OPIs operational performance indicators RIFs risk influencing factors ROP rate of penetration ROV remote operated vehicle RPM rotation per minute SINTEF Stiftelsen for industriell og teknisk forskning or 'The Foundation for Scientific and Industrial Research' TFs technical factors WOB weight on bit WOC weight on cement